Propiocepción como tratamiento rehabilitador del paciente con ictus - Bonilla Acosta, Viviana Mikaela (2022)
ABSTRACT: The research project was carried out in the bibliographic review modality to reveal the effects that proprioception has when it intervenes in the rehabilitation of patients with a stroke process and determine the contribution it has for motor actions in the human body; thus, being included in rehabilitation and preventive protocols for cerebrovascular accidents or stroke. These investigations were based on various Physiotherapy, Neurology, Google Scholar Scielo, PubMed, Scielo, and El Sevier journals. According to the established exclusion criteria and assessment of the articles on the PEDro scale, the articles considered suitable for the study were 35 since they met a score equal to or greater than six on the PEDro scale. They are in different languages such as English and Portuguese translated into Spanish. At the end of the study, it was possible to fulfill the objective set in the research, to base the effects of proprioception in the rehabilitative treatment of the patient with stroke, through an exhaustive bibliographic search, for the deepening of the knowledge of these motor actions and prevention of cerebrovascular accidents or stroke.